Challenges in optimizing a prostate carcinoma binding peptide, identified through the Phage display technology - Askoxylakis, Vasileios; Zitzmann-Kolbe, Sabine; Zoller, Frederic; Altmann, Annette; Markert, Annette; Rana, Shoaib; Marr, Annabell; Mier, Walter; Debus, Jürgen; Haberkorn, Uwe (Molecules, 2011)
The transfer of peptides identified through the phage display technology to clinical applications is difficult. Major drawbacks are the metabolic degradation and label instability. The aim of our work is the optimization of DUP-1, a peptide which was identified by phage display to specifically target human prostate carcinoma. To investigate the influence of chelate conjugation, DOTA was coupled to DUP-1 and labeling was performed with 111In. To improve serum stability cyclization of DUP-1 and targeted D-amino acid substitution were carried out. Alanine scanning was performed for identification of the binding site and based on the results peptide fragments were chemically synthesized. The properties of modified ligands were investigated in in vitro binding and competition assays. In vivo biodistribution studies were carried out in mice, carrying human prostate tumors subcutaneously. DOTA conjugation resulted in different cellular binding kinetics, rapid in vivo renal clearance and increased tumor-to-organ ratios. Cyclization and D-amino acid substitution increased the metabolic stability but led to binding affinity decrease. Fragment investigation indicated that the sequence NRAQDY might be significant for target-binding. Our results demonstrate challenges in optimizing peptides, identified through phage display libraries, and show that careful investigation of modified derivatives is necessary in order to improve their characteristics.
Gesehen am 23.03.2022